2021
DOI: 10.32890/ijbf2022.17.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Does Economic Policy Uncertainty Reduce Financial Inclusion?

Abstract: This study investigates whether the level of economic policy uncertainty (EPU) would reduce the level of financial inclusion. It was predicted that a high level of EPU could have a negative effect on the level of financial inclusion. It was argued that a high level of EPU would discourage financial institutions from providing basic financial services to low end customers and unbanked adults, and this would lead to a decrease in the level of financial inclusion. Using a sample of 22 countries, the study found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…More precisely, a 1% increase in EPU in BRIC nations can result in a reduction in the institutional quality by a coefficient of -0.1876% in Brazil, -0.2380% in China, -0.1702% in India, and -0.3601% in Russia. Ozili, (2021) reported that increased EPU led to pain for financial institutions since the cumulative repercussions of nonperforming loans increase with increasing EPU degree. EPU negatively impacts families and individuals that rely on the services and products provided by financial institutions.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, a 1% increase in EPU in BRIC nations can result in a reduction in the institutional quality by a coefficient of -0.1876% in Brazil, -0.2380% in China, -0.1702% in India, and -0.3601% in Russia. Ozili, (2021) reported that increased EPU led to pain for financial institutions since the cumulative repercussions of nonperforming loans increase with increasing EPU degree. EPU negatively impacts families and individuals that rely on the services and products provided by financial institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies identify some determinants of financial inclusion such as digital finance (Ozili, 2018), financial literacy (Grohmann et al. , 2018), financial regulation (Anarfo and Abor, 2020), economic policy uncertainty (Ozili, 2022), etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The priority given to financial inclusion by governments is hinged on substantial research that shows evidence that financial inclusion promotes economic growth (Kim et al, 2018), greater financial stability (Neaime and Gaysset, 2018), poverty reduction (Koomson et al, 2020), reduction in income inequality (Huang and Zhang, 2020) and mitigating financial risk (Ozili, 2021b), among others. Other studies identify some determinants of financial inclusion such as digital finance (Ozili, 2018), financial literacy (Grohmann et al, 2018), financial regulation (Anarfo and Abor, 2020), economic policy uncertainty (Ozili, 2022), etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings suggest that monetary policy affects financial inclusion, and monetary policy is also influenced by financial inclusion. Ozili (2022) shows that high economic policy uncertainty reduces the level of financial inclusion. Myers et al (2012) point out that in countries like Ireland, Spain, Canada and the UK, credit unions owned by members play a significant role in reaching under-served and excluded communities even though credit unions faced financial and operational problems.…”
Section: Review Of the Policy Literaturementioning
confidence: 99%